Properties and Sensing Performance of THz Metasurface Based on Carbon Nanotube and Microfluidic Channel - Wang, Yue; Zhang, Xiaoju; Zhou, Tao; Zhu, Yongqiang; Cui, Zijian; Zhang, Kuang (Frontiers in Physics, 2021)
Carbon-based metamaterials are expected to lead to biological and chemical sensing because of their fast electron transfer rate, good biocompatibility, and high absorption ratios. In this work, we integrate carbon nanotubes metasurface (CM) and microfluidic channel (MC) for a composite terahertz (THz) metasurface (CMMC). The absorption properties and sensing performance of the proposed composite metasurface have been studied. It is observed that the absorption is nearly 71.8% at 0.96 THz and 92.4% at 1.65 THz, respectively. The variation of response with refractive index of the analytes for the proposed CMMC is investigated and it is found that the frequency and intensity of the low frequency resonance absorption peak decrease obviously with the increase of the refractive index of the analytes. Owing to the coupling of the CM and MC in the microfluidic channel, the interaction between the incident THz wave and analytes has been enhanced, and the frequency and intensity sensitivities has achieved 254 GHz/RIU and 314/RIU, respectively. In addition, the influence of the structural parameters of the proposed CMMC on the absorption characteristics is also studied in detail. The results shown that the absorption properties of the CMMC can be adjusted by changing the structural parameters, which will provide a guideline for design. The proposed CMMC will facilitate the realization of carbon nanotube metamaterials sensing applications, and, when combined with microfluidic channel, will lead to large-area THz biological and chemical sensing.